2022
DOI: 10.3390/ijerph19042349
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Sepsis Onset Using Neural Architecture Search Based on Genetic Algorithms

Abstract: Sepsis is a life-threatening condition with a high mortality rate. Early prediction and treatment are the most effective strategies for increasing survival rates. This paper proposes a neural architecture search (NAS) model to predict the onset of sepsis with a low computational cost and high search performance by applying a genetic algorithm (GA). The proposed model shares the weights of all possible connection nodes internally within the neural network. Externally, the search cost is reduced through the weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Nemati et al [ 35 ] achieved an AUROC of 0.85 with a modified Weibull-Cox proportional hazards model for predicting sepsis 6 hours in advance, and Yang et al [ 28 ] achieved similar performance, also with the XGBoost algorithm. Kim et al [ 36 ] recently developed a type of deep learning model to predict sepsis that had higher discrimination performance than our model, with an AUROC of 0.91. However, their model could be seen as a complex black box due to its lack of interpretability, which might limit its acceptance among clinicians.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nemati et al [ 35 ] achieved an AUROC of 0.85 with a modified Weibull-Cox proportional hazards model for predicting sepsis 6 hours in advance, and Yang et al [ 28 ] achieved similar performance, also with the XGBoost algorithm. Kim et al [ 36 ] recently developed a type of deep learning model to predict sepsis that had higher discrimination performance than our model, with an AUROC of 0.91. However, their model could be seen as a complex black box due to its lack of interpretability, which might limit its acceptance among clinicians.…”
Section: Discussionmentioning
confidence: 95%
“…However, model calibration decreased as the prediction window shortened, which might be associated with a decreasing number of positive steps due to the reduction of the prediction window. Several studies have reported a similar trend for AUROC across different prediction windows but have not reported changes in AUPRC or calibration [ 35 , 36 ]. Most importantly, a model with good discrimination and calibration performance does not necessarily have high clinical value [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most ML frameworks require determining the time of sepsis onset ( T 0 ) or the initiation of a period when patterns are consistent with sepsis as a distinct entity. Kim et al (33) recently adopted this approach. Larie et al (34) implemented ANNs using long short-term memory (LSTM) and multilayer perceptrons for sepsis prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning algorithms have also shown promise in analyzing medical time series data despite the challenge of dealing with sensor- and noise-based errors (33). However, small sample sizes can lead to overfitting, which can be addressed using self-supervised learning, transfer learning, or data augmentation (49).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation